THE INTERPLAY BETWEEN ESG CONTROVERSIES AND INNOVATION ON FIRM FINANCIAL PERFORMANCE: EVIDENCE FROM INDONESIA - Sintia Farach Dhiba; Dewi Izzatul Lailatil Muthohiroh; Rizky Eriandani (Jurnal Bisnis dan Akuntansi, 2025)
This study aims to examine the impact of Environmental, Social, and Governance (ESG) controversies and innovations on firm financial performance. A total of 522 firm-year observations of Indonesia’s publicly listed non-financial companies from 2019 to 2023 were collected using purposive sampling. Data is generated from Refinitiv Eikon Database and analyzed through multiple linear regression (ordinary least squares). The findings reveal that ESG non-controversy has a consistent and significant positive effect on firm value, underscoring its role in preserving legitimacy and signaling firm’s quality. ESG innovation also shows a positive association with firm value in the full sample but loses statistical significance in sub-sample analyses split by firm size, suggesting its signaling value may be context-dependent. Firms are advised to actively minimize controversies while fostering innovative approaches to ESG initiatives, as these factors are shown to play a critical role in increasing financial performance. In contrast to existing Indonesian ESG research that aggregates ESG metrics into a single score, this study examines ESG controversies and ESG innovation as separate dimensions and concurrently exploring their impacts on firm value through the frameworks of signalling and legitimacy theory. The results offer practical insights for managers aiming to integrate ESG into corporate strategy and for investors evaluating ESG signals in valuation decisions.